Impact of comorbidities on outcomes of elderly patients with diffuse large B‐cell lymphoma. Issue 10 (19th July 2017) - Saygin, Caner; Jia, Xuefei; Hill, Brian; Dean, Robert; Pohlman, Brad; Smith, Mitchell R.; Jagadeesh, Deepa
Abstract: International prognostic index (IPI) has remained the primary prognostic tool in diffuse large B cell lymphoma (DLBCL) for more than 20 years. Even though the disease is more common in older population, the impact of comorbidities, dose reductions, and treatment‐related adverse events (TAEs) on the outcome in elderly DLBCL patients has not been well established. We studied 413 consecutive patients aged ≥ 60 years who were treated at the Cleveland Clinic. The median age at diagnosis was 69 years, 58% of patients had high IPI score, and 85% had low Charlson comorbidity index (CCI). Forty percent of patients required dose reductions during treatment, 78% achieved CR, and 70% experienced at least one grade II‐IV TAE. High IPI score, high CCI, reduced dose chemotherapy, TAE, and hospitalization were significant predictors of death and relapse. In multivariable analysis, high IPI and CCI were independent predictors of overall and progression free survival. A simple model combining IPI and CCI could reliably distinguish three prognostically separate risk groups. Our results suggest that incorporation of CCI in current prognostic models can improve prognostication of older DLBCL patients and CCI might be a valuable tool in evaluating the eligibility of older patients for clinical trial enrollment.